Mentha pulegium crude extracts induce thiol oxidation and potentiate hemolysis when associated to t-butyl hydroperoxide in human’s erythrocytes - MATHEUS C. BIANCHINI; DENNYURA O. GALVÃO; TATIANA TAMBORENA; CLAUDIA O. ALVES; ROBSON L. PUNTEL (Anais da Academia Brasileira de Ciências, 2017)
ABSTRACT Mentha pulegium (Lamiaceae) tea has been used as a traditional medicine; however, the modulatory effect of M. pulegium extracts on damage to human erythrocytes associated to t-butyl hydroperoxide (t-BHP) exposure remains to be investigated. Accordingly, we perform this study in order to test the hypothesis that aqueous and ethanolic extracts of M. pulegium could modulate the hemolysis associated to t-BHP exposure, non-protein thiol (NPSH) oxidation and lipid peroxidation (measured as thiobarbituric acid reactive substances - TBARS) in human erythrocytes. Samples were co-incubated with t-BHP (4 mmol/L) and/or aqueous or ethanolic extracts (10-1000 mg/mL) during 120 min to further analysis. We found that both extracts, when associated to t-BHP, potentiate NPSH oxidation and hemolysis. Moreover, both extracts significantly prevents against t-BHP-induced TBARS production. A significant correlation among hemolysis and NPSH levels was found. Taking together, our data points that the association of M. pulegium extracts with t-BHP culminates in toxic effect to exposed erythrocytes, besides its protective effect against t-BHP-induced TBARS production. So, we infer that the use of this extract may exert negative effect during painful crisis in sickle cell anemia. However, more studies are still necessary to better investigate/understand the mechanism(s) involved in the toxic effect resultant from this association.